2006
DOI: 10.1007/s10802-006-9082-3
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Change in Parenting Stress Across Early Childhood: Child and Maternal Factors

Abstract: This study examined maternal parenting stress in a sample of 430 boys and girls including those at risk for externalizing behavior problems. Children and their mothers were assessed when the children were ages 2, 4, and 5. Hierarchical linear modeling (HLM) was used to examine stability of parenting stress across early childhood and to examine child and maternal factors predicting parenting stress at age 2 and changes in parenting stress across time. Results indicated that single parenthood, maternal psychopat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
204
2
10

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 288 publications
(244 citation statements)
references
References 50 publications
20
204
2
10
Order By: Relevance
“…Studies examining children's behavior problems and parenting stress across time have found significant correlations between these variables (Shaw et al, 1998;Williford et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies examining children's behavior problems and parenting stress across time have found significant correlations between these variables (Shaw et al, 1998;Williford et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Future research could examine the predictive nature parenting stress and protective factors have on one another. Similar to studies examining the changes in parenting stress and behavior problems in children over time (e.g., Williford et al, 2007), research could examine changes in parenting stress and protective factors in children over time. This would illustrate whether initial parenting stress levels or protective factors levels predict an increase, decrease, or maintenance of the other.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using cross-sectional data sets have found that it is difficult to comprehend how parenting stress and attitudes change over time and with changes in the children's age. Most cross-sectional research has emphasized the importance of studying aspects of behavior and individual differences that change over time [10,17,18]. As the parent-child relationship lasts for a lifetime and the qualities of such relationships have strong long-term and progressive influences [19], it is particularly important to observe the effects of parenting stress and controlling parenting attitudes on the problem behaviors of children over the long-term.…”
Section: Introductionmentioning
confidence: 99%
“…Literatürde anne-babalık rollerinden kaynaklanan anne-baba stresinin ölçülmesi amacıyla yaygın bir şekilde kullanılan ABSÖ-KF, 10'dan çok dile uyarlanmış ve anne-baba stresi ile ilgili araştırmalarda tüm dünyada yaygın olarak kullanılmaktadır. [11][12][13][14] Bu çalışmanın amacı, daha önce Türkçeye uyarlanan ABSÖ'nün kısa formunun Türkçeye uyarlanması ve ölçeğin geçerlilik ve güvenilirlik çalışmasının yapılmasıdır. 15 klinik gruplar arasında tüm alt boyutlarda p<0.001 düzeyinde anlamlı farklılık göstermek-tedir.…”
Section: Introductionunclassified